2017
DOI: 10.9775/kvfd.2016.16371
|View full text |Cite
|
Sign up to set email alerts
|

Çin Tibet Koyununda Myogenin Geninin Genetik Polimorfizmi ve Büyüme Özellikleriyle Olan İlişkisi

Abstract: Myogenin gene encodes for skeletal muscle-specific transcription factors with highly conserved basic helix-loop-helix domain and play key role in growth and muscle development. In this study, the polymorphisms of myogenin gene were investigated to check whether they are associated with growth traits in Chinese-Tibetan sheep. In three sheep breeds with a total number of 632 individuals, three SNPs, including two in exon 1 (C109A and C183T) and one in intron 2 (A1403C) were found by DNA sequencing. Among those, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Analyses of this gene were also performed within the Bovidea family, but with contradictory results. Some authors reported association with some important economically relevant body measurement (Bhuiyan et al, 2009, Xue et al, 2011, Sun and Han, 2017, while others reported lack of association between SNPs and growth traits (Abu El-Magd et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analyses of this gene were also performed within the Bovidea family, but with contradictory results. Some authors reported association with some important economically relevant body measurement (Bhuiyan et al, 2009, Xue et al, 2011, Sun and Han, 2017, while others reported lack of association between SNPs and growth traits (Abu El-Magd et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Reports have shown that SNPs within this gene in swine (Kapelański et al, 2005;Kim et al, 2009), cattle (Xue et al, 2011), sheep (Sun and Han, 2017) and chickens (Wei et al, 2016) influence growth traits. However most of the SNPs analysed were synonymous, intronic or 3' region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work revealed that SNPs of candidate (i.e., GH and Myogenin) significantly influenced growth traits in Tibetan sheep [7,15] . Multi-marker interaction analysis suggested the influence of the mutations in three different genes were additive effects, which is not consistent with the the function of GHRH in regulating the GH secretion.…”
Section: Discussionmentioning
confidence: 99%
“…were designed by Primer Premier Software (Version 5.0). PCR amplification was performed following the method of Sun et al [7] Amplification were then sequenced using an ABI 3730 sequencer (ABI, Foster City, CA, USA).…”
Section: Methodsmentioning
confidence: 99%